2021
DOI: 10.15252/embr.201949651
|View full text |Cite
|
Sign up to set email alerts
|

Transient deSUMOylation of IRF2BP proteins controls early transcription in EGFR signaling

Abstract: Molecular switches are essential modules in signaling networks and transcriptional reprogramming. Here, we describe a role for small ubiquitin‐related modifier SUMO as a molecular switch in epidermal growth factor receptor (EGFR) signaling. Using quantitative mass spectrometry, we compare the endogenous SUMO proteomes of HeLa cells before and after EGF stimulation. Thereby, we identify a small group of transcriptional coregulators including IRF2BP1, IRF2BP2, and IRF2BPL as novel players in EGFR signaling. Comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Our data indicate that, in addition to the RING domain, both DNA binding and nuclear localization are required for IRF2BPL-mediated inhibition of Wnt transcription. Hence, Pits/IRF2BPL, like their paralogs (IRF2BP1 and IRF2BP2), likely act as transcriptional repressors ( 57 , 65 , 66 ) to inhibit Wnt transcription, consistent with the increase in wg/ wnt1/WNT1 messages observed in flies, fish, and human cells. CkIα has also been documented to be in nuclear speckles where active gene regulation occurs ( 59 ).…”
Section: Discussionsupporting
confidence: 52%
“…Our data indicate that, in addition to the RING domain, both DNA binding and nuclear localization are required for IRF2BPL-mediated inhibition of Wnt transcription. Hence, Pits/IRF2BPL, like their paralogs (IRF2BP1 and IRF2BP2), likely act as transcriptional repressors ( 57 , 65 , 66 ) to inhibit Wnt transcription, consistent with the increase in wg/ wnt1/WNT1 messages observed in flies, fish, and human cells. CkIα has also been documented to be in nuclear speckles where active gene regulation occurs ( 59 ).…”
Section: Discussionsupporting
confidence: 52%
“…For example, combining SILAC (stable isotope labeling by amino acids in tissue culture), quantitative mass spectrometry and SUMO-IP (SUMOylated proteins immunoprecipitation), permitted the discovery of a switch instigated by small ubiquitin-related modifier (SUMO). The investigators identified the endogenous SUMOylated proteins of HeLa cells after EGF stimulation [ 120 ]. This uncovered a group of transcriptional coregulators, including IRF2BP1, IRF2BP2, and IRF2BPL, which are involved in the EGFR signaling pathway.…”
Section: Proteomic and Epigenetic Analyses Of Egf-induced Molecular Switchesmentioning
confidence: 99%
“…Furthermore, Barysch et al (2021) investigated the functional consequences of endothelial growth factor (EGF)-dependent deSUMOylation of IRF2BP2 protein. They demonstrated that IRF2BP2 protein lost SUMO upon EGF treatment in HeLa cells and this deSUMOylation is very transient.…”
Section: Irf2bp2 In Cell Proliferationmentioning
confidence: 99%
“…Two SUMO motifs that were conserved within the family IRF2BP have been identified, one of which is located in the C-terminal region. IRF2BP2 knockdown in HeLa cells led to an upregulation of EGFR which may contribute to enhanced proliferation in response to EGF, a potent regulator of cellular growth as well as in cancer progression ( Barysch et al, 2021 ).…”
Section: Irf2bp2 In Cell Proliferationmentioning
confidence: 99%